PENINGKATAN KEMAMPUAN DESAIN GRAFIS SISWA MTS NEGERI 2 MAGELANG MELALUI PELATIHAN CORELDRAW - Fikri, Zaki; Purwanto, Purwanto; Syarifah, Laili; Puspitasari, Dakusta (Jurnal Pepadu, 2024)
Technological developments and advances emphasize the critical role of schools in adapting themselves to the challenges of today's digital world. The service activities at MTS Negeri 2 focus on increasing partners' abilities in graphic design, especially creating logos, covers, and flayers using the CorelDRAW application. This activity aims to improve students' hard skills in graphic design, especially at the class IX level. The method implemented involves a lecture approach, discussion, and direct assistance through practicum using the CorelDRAW application. This activity also includes evaluation through case study assignments, which require students to create a logo, cover, and flayer. Thus, a holistic learning approach ensures students' understanding and practical application in responding to technological advances in this digital era. From the results of distributing questionnaires and evaluating graphic design skills training activities, 90% of participants succeeded in creating logos, cover designs, and flyers. Apart from that, participants can also apply more than one application in the graphic design process.